An Aesthetic Interpretation of the Pilates Method: its principles and convergences with somatic education - Odilon José Roble (Universidade Estadual de Campinas, UNICAMP, Campinas, Brazil) (Revista Brasileira de Estudos da Presença, 2014)
The Pilates method, originally called contrology, has been gaining a significant following in Brazil. This article discusses the method’s principles and convergences with somatic education by analyzing the original works of Joseph Pilates using an aesthetic-philosophical approach. It seems implicit that the Pilates method can be instrumental for the performing arts, and the article accordingly points to some connections in this regard. However, the article also argues that, in the absence of the guiding principles proposed by Pilates, the method ceases to be an art of control and instead is reduced to something not much different from other physical exercises.